2022
DOI: 10.3855/jidc.16485
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and distribution of pathogenic genes in Campylobacter jejuni isolated from poultry and human sources

Abstract: Introduction: Campylobacter jejuni is one of the most common bacterial causes of human gastroenteritis. Despite its public health importance, the virulence factors and mechanisms underlying C. jejuni pathogenesis remain poorly understood and the relationships between these genes and the sources of the strains are not clear. We aimed to determine the virulence profiles of C. jejuni isolated from poultry and human cases of Campylobacteriosis. Methodology: A total of 50 strains of C. jejuni isolated from po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…But it was 25%, 33.3%, and 50% in chickens, ducks, and pigeons respectively. other studies revealed higher percentages of 53.8% and 66% [49,14], Conversely, [50] mentioned the incidence of the iam gene was (4%) regardless of the source of isolation. Also, in Poland [51] and Canada [52] many studies were completed and clarified that the iam locus gene has been detected in 54.7% and 57.1% of C. jejuni chicken isolates, respectively, and those results appeared higher detection rate than our results (25%) for chicken.…”
Section: Discussionmentioning
confidence: 87%
“…But it was 25%, 33.3%, and 50% in chickens, ducks, and pigeons respectively. other studies revealed higher percentages of 53.8% and 66% [49,14], Conversely, [50] mentioned the incidence of the iam gene was (4%) regardless of the source of isolation. Also, in Poland [51] and Canada [52] many studies were completed and clarified that the iam locus gene has been detected in 54.7% and 57.1% of C. jejuni chicken isolates, respectively, and those results appeared higher detection rate than our results (25%) for chicken.…”
Section: Discussionmentioning
confidence: 87%
“…A previous study by Moreira Lima et al . [ 10 ] on birds have identified the link between campylobacteriosis and environmental fecal contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Human campylobacteriosis arising from food sources has been extensively studied, whereas environmental risk factors such as exposure to fecal material from animals have been understudied [9]. A previous study by Moreira Lima et al [10] on birds have identified the link between campylobacteriosis and environmental fecal contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne pathogens and antibiotics have been reported to impact the human health negatively. Outbreaks linked to foodborne infections have become increasingly complex and challenging due to the emergence of multidrug-resistant (MDR) bacteria, such as Clostridium infections and Campylobacteriosis in humans [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Concerns have been raised about the development of alternative approaches to disease control and prevention in animal husbandry.…”
Section: Introductionmentioning
confidence: 99%